2010
DOI: 10.1016/j.npep.2010.04.001
|View full text |Cite
|
Sign up to set email alerts
|

Alarin stimulates food intake in male rats and LH secretion in castrated male rats

Abstract: Alarin is a newly identified member of the galanin family of neuropeptides that includes galaninlike peptide (GALP) and galanin. Alarin was discovered as an alternate transcript of the GALP gene in neuroblastoma cells, and subsequently alarin mRNA was detected in the brain of rodents. GALP and galanin are important central regulators of both feeding and reproductive behavior. We hypothesized, that, as a member of the galanin family of peptides, alarin would also have central effects on feeding and reproduction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
81
0

Year Published

2011
2011
2014
2014

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 47 publications
(83 citation statements)
references
References 57 publications
(79 reference statements)
2
81
0
Order By: Relevance
“…The data shown are the meansGS.E.M. *P!0.05, **P!0.01 vs NCs; C P!0.05, CC P!0.01 vs DCs; # P!0.05 vs alarin group; body weight of animals (Boughton et al 2010, Van Der Kolk et al 2010, Fraley et al 2012. The alarin-induced gain of body weight in mice could be due to not only an increase in food and water intake, but also a decrease in excretion of feces and urine, and metabolic rate (Fraley et al 2012).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The data shown are the meansGS.E.M. *P!0.05, **P!0.01 vs NCs; C P!0.05, CC P!0.01 vs DCs; # P!0.05 vs alarin group; body weight of animals (Boughton et al 2010, Van Der Kolk et al 2010, Fraley et al 2012. The alarin-induced gain of body weight in mice could be due to not only an increase in food and water intake, but also a decrease in excretion of feces and urine, and metabolic rate (Fraley et al 2012).…”
Section: Discussionmentioning
confidence: 99%
“…A study with the anti-alarin antibody revealed alarin-like immunoreactivity in the locus coeruleus and subcoeruleus (Eberhard et al 2012). Using anterograde tracing, the projections from the hypothalamus to the locus coeruleus have been found (Van Der Kolk et al 2010). These areas of the brain are implicated in the regulation of appetite and food intake (Boughton et al 2010).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Synthetic alarin inhibits neurogenic inflammation of the skin and has actions typical of a neuropeptide in that it regulates food intake, metabolism, reproductive behavior, and hormone secretion (Boughton et al, 2010;Van Der Kolk et al, 2010;Fraley et al, 2012Fraley et al, , 2013. Furthermore, alarin has antidepressant-like effects that are Galanin Family Peptides and Receptors associated with reduced serum levels of corticotrophinreleasing hormone, adrenocorticotropic hormone, and corticosterone .…”
mentioning
confidence: 99%